Utilisation of brown trout by Acanthocephalus clavula (Acanthocephala) in brown trout (Salmo trutta) in an Irish lake: is this evidence of a host shift? - HOLLAND, CELIA (My University, 2004)
The population biology of the fish acanthocephalan Acanthocephalus clavula was described from 161 wild brown trout, Salmo trutta sampled over a two-year period in Clogher Lake in the west of Ireland. Overall prevalence of the parasite was 86% and the mean abundance was 53 worms per fish. Despite the presence of large numbers of worms in the trout very few females (2%) attained full reproductive maturity. This suggests that trout is an accidental host. A sample of yellow eels, Anguilla anguilla was examined at a different time from the same lake. The prevalence of A. clavula was 97% and the average abundance was 8 worms per fish. In contrast to the situation in trout, the proportion of female worms attaining full reproductive maturity was 61% fulfilling the expected characteristic of a preferred definitive host. The possible explanations for the very high abundance of A. clavula in trout are discussed and include the influence of fluctuations in host populations, host diet and the absence of a potential competitor.
PUBLISHED
Keywords: Zoology; Acanthocephalus clavula; trout